The Influence of Empowering Leadership and Talent Management on Employees' Performance Through Job Satisfaction as Intervening Variable - Zulkifli Zulkifli; Ahmad Ahmad; M. Yusuf Alfian Rendra Anggoro KR (International Journal of Economics Development Research (IJEDR), 2023)
This research aimed to determine the influence of empowering leadership and talent management on employees' performance through job satisfaction at PT. Pelindo Terminal Petikemas New Makassar. The type of research used was quantitative research. The population in this research data were all employees of PT. Pelindo New Makassar Container Terminal as many as 135 persons. The number of samples used were 101 persons using the proportional stratified random sampling method.Based on the results of research using the AMOS 24 program, it can be concluded that empowering leadership got a significant positive influence on job satisfaction, talent management brought a significant positive influence on job satisfaction, empowering leadership has influence on employees' performarice, talent management has influence on employees' performance, empowering leadership brought influence on performance through satisfaction work, and talent management had positive and significant influence on performance through job satisfaction.